The spread of the phenomenon of atheism and ways to resist it - Allaw, Abdulhameed Abdo Mohsen (Journal of Islamic Sciences, 2023)
Atheism is a phenomenon that afflict human societies, especially in the present era. The idea of atheism is based on criticizing religions and not recognizing them, and its idea depends on a number of philosophical, social and historical arguments.  Recently, large numbers of Muslim children adopted this phenomenon and openly call for it, so there was a defect in belief and a lot of doubt and atheism, which caused confusion and led to deviant thought. This phenomenon has contributed to chaos, skeptical beliefs and spread suspicions.  In view of the seriousness of the phenomenon of atheism and its negative results, the researcher worked on explaining this phenomenon, its components, causes and effects, and showed ways to confront it.  To demonstrate this, the researcher followed the analytical inductive approach, in addition to the comparative approach, due to its compatibility with the research objectives. He focused on including the main axes of atheism, its components, and the reasons for the spread of this phenomenon.  The researcher concluded the research by clarifying ways to combat this phenomenon, concluding with the most important findings and recommendations that he achieved through the study. The most important findings and recommendations were that there are special reasons for the spread of the phenomenon of atheism in our Arab and Islamic societies, including religious extremism, hatred instilling in the name of religion, and the cult of some personalities. In addition to the previous reasons, some people engage in the issues of fate and the existence of evil on earth, lack of purification of souls, and indulgence in desires as well as cultural superficiality.  The study also recommended the importance of combating this phenomenon to get rid of and limit its spread in all possible ways and methods, whether by individuals or by groups and governments.
Keywords: phenomenon; spread; skepticism; suspicions; atheism